Examining the Efficacy of Bright Light Therapy on Cognitive Function in Hematopoietic Stem Cell Transplant Survivors. Issue 5 (October 2022) - Wu, Lisa M.; Valdimarsdottir, Heiddis B.; Amidi, Ali; Reid, Kathryn J.; Ancoli-Israel, Sonia; Bovbjerg, Katrin; Fox, Rina S.; Walker, Lauren; Matharu, Amreen; Kaseda, Erin T.; Galvin, John P.; Adekola, Kehinde; et al.
Patients who have undergone hematopoietic stem cell transplant (HSCT) may experience cognitive impairment that can persist after treatment. Several studies have shown that bright light therapy may improve cognition, potentially due to its effects on the circadian system via brain regions that respond preferentially to light. In this double-blind randomized controlled trial, the efficacy of bright light therapy on cognition was examined in HSCT survivors. Forty-seven HSCT survivors at an urban hospital in the United States were screened for mild cognitive impairment, randomized to either bright white light (BWL) or comparison dim red light (DRL) conditions using a block randomization approach, and instructed to use their assigned light box every morning upon awakening for 30 min for 4 weeks. Assessments occurred at baseline, the end of the second week of the intervention, the end of the intervention, and at follow-up (8 weeks later). The primary outcome was objective cognitive function as measured by a global composite score on neuropsychological tests. Secondary outcomes included cognitive performance in individual domains, self-reported cognitive function, fatigue, sleep and sleep quality, and circadian rhythm robustness. Repeated-measures linear mixed models for both objective and self-reported cognitive function indicated significant main effects for time ( p s < 0.05) suggesting significant improvements in both conditions over time. Time by light condition interaction effects were not significant. Models focused on secondary outcomes yielded no significant effects. Both BWL and DRL groups demonstrated significant improvements in objective cognitive and self-reported cognitive function over time, but there was no hypothesized effect of BWL over DRL nor associations with circadian rhythm robustness. Therapeutic effects of both light conditions, practice effects, and/or placebo effects may account for the findings. Trial registration: ClinicalTrials.gov Identifier: NCT02677987 (9 February 2016)